TANGGUNGJAWAB ORANG TUA DALAM PEMBINAAN KEIMANAN PADA ANAK REMAJA DI KECAMATAN PEUDADA BIREUEN - Nurbayani Nurbayani (UIN AR-RANIRY, 2017)
This paper intends to give an idea of the importance of teaching the faith practiced in everyday life. Parents as primary educators in the family not only provide adequate nutrition, food clothing only to children, but also meet the spiritual aspect as a spiritual need. Therefore, this study examines the efforts of parents in fostering the religious life of the child in the Peudada sub-district. The research method used is descriptive with qualitative approach, with research subject five people that is parent active in majilis activity. Technique of data collecting through deep interview, observation and documentation. While data analysis is done by presenting data in the form of a systematic narrative. The results showed that the form of fostering of faith conducted by parents against adolescents is 1) fostering teenagers to believe in God 2) inculcate the spirit of solemnity in worshiping God, 3) inculcate the spirit of feeling watched by God.